As possíveis consequências da declaração de (in)constitucionalidade do ensino religioso público pelo Supremo Tribunal Federal na ação direta de inconstitucionalidade nº 4439/2010 - Bastos, Nívea Amazonas Pereira (2014)
The Brazilian Constitution says that Religious Education (RE) should be a curricular component in the public basic education schools, but it also points out that the enrollment should be optional. The offering of RE is not understood in a unified way. To some, the obligation to offer RE in public schools and the fact that professors of any religious background can teach this discipline is inconvenient and transforms the public school space into a mere space of religious catechism and proselytism, used by Catholics or by any influential religious confession. And the consequence of it being mandatory is a loss for students with atheist, agnostic perspectives or perspectives of any religious denomination with less power in the social-political sphere, and to the constitutional principle of secularism. The present paper has the objective of analyzing the possible legal effects of the judgement of the constitutionality of Religious Education in Brazilian public schools by the Federal Supreme Court, and facing the controversy of the theme, we will study [Religious Education] from its beginning until today, verifying if the way it is implemented in Brazil has or does not have the power to indoctrinate, catechise or serve as a form of domination, or if the teaching is given based on ethical and moral principles, that can and should be part of all and any religion, in respect to the legitimate right of the individual to have access to the teaching of religion and of ethics.